Human airway trypsin‐like protease exerts potent, antifibrotic action in pulmonary fibrosis. Issue 3 (3rd January 2018) - Menou, Awen; Flajolet, Pauline; Duitman, JanWillem; Justet, Aurélien; Moog, Sophie; Jaillet, Madeleine; Tabèze, Laure; Solhonne, Brigitte; Garnier, Marc; Mal, Hervé; Mordant, Pierre; Castier, Yves; et al.
Abstract : Idiopathic pulmonary fibrosis (IPF) is characterized by the deposition of excessive extracellular matrix and the destruction of lung parenchyma, resulting from an aberrant wound‐healing response. Although IPF is often associated with an imbalance in protease activity, the mechanisms underlying the sustained repair mechanisms are not fully understood. Here, we addressed the role of the recently identified, membrane‐anchored serine protease human airway trypsin‐like protease (HAT). In the present study, we show that both HAT expression and activity were up‐regulated in human IPF specimens. Next, adenoviral overexpression of HAT before bleomycin challenge attenuated lung injury as well as extracellular matrix deposition in the bleomycin‐induced pulmonary fibrosis model. In vitro, HAT prevented specific fibrosis‐associated responses in primary human pulmonary fibroblasts and induced the expression of mediators associated with the prostaglandin E2 pathway. Altogether, our findings suggested that HAT could have a protective role in IPF and other fibrotic lung disorders.—Menou, A., Flajolet, P., Duitmen, J., Justet, A., Moog, S., Jaillet, M., Tabèze, L., Solhonne, B., Garnier, M., Mal, H., Mordant, P., Castier, Y., Cazes, A., Sallenave, J.‐M., Mailleux, A. A., Crestani, B. Human airway trypsin‐like protease exerts potent, anti‐fibrotic action in pulmonary fibrosis. FASEB J. 32, 1250‐1264 (2018). www.fasebj.org